The validity of D-MENBOLA: Digitalization of football learning media based on articulate storyline 3 - I Wayan Artanayasa; Adrianus I Wayan Ilia Yuda Sukmana; Ketut Chandra Adinata Kusuma (Journal Sport Area, 2022)
The COVID-19 pandemic has an impact on the learning process in all educational units, including higher educational units. This situation requires educators to be more creative and innovative in using learning media to transform knowledge and skills to their students. This study aims to describe the validity of interactive learning media based on articulate storyline 3 in the theory and practice of football coaching. This research included development research by adopting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The data collection instrument used a questionnaire that referred to the LORI (Learning Object Review Instrument) standard. The LORI standard consists of nine aspects of assessment, namely content quality, direction of learning objectives, feedback and adaptation, motivation, display design, interaction use, accessibility, development capabilities, and standard fulfillment. The data analysis technique used is descriptive quantitative and qualitative. The results showed that the level of feasibility/validity of the learning media named D-MENBOLA or digitalization of football learning media based on articulate storyline 3 iss declared very feasible/very valid. Based on these result, D-MENBOLA can then be used in the theory and practice of football coaching as one of the innovative learning media.